Land and Credit Market in a Bodo Village of Assam - Daimari, Mizinksa (My University, 2021)
The Bodos, as peasants, have featured significantly in the colonial agrarian history of Assam. However, there is a massive research gap on the transformations surrounding the Bodo peasantry in more contemporary times. The plains tribes of Bodos, despite a long history of identity politics, cannot be claimed as a homogenous group. Private ownership of land, which marks capitalist agriculture, features significantly among the Bodo peasantry. A free land, labour, and credit market are the mainstay of capitalist agriculture. How has capitalist agriculture advanced and transformed the Bodo peasantry in recent times? This thesis studies agrarian relations among the Bodo community through an examination of the land and credit market in an all Bodo village of Assam. The objective of this research is to investigate the socio-economic differences within the Bodo peasantry as opposed to discontentment between the Bodos and others. The fieldwork is in an exclusively Bodo dominated revenue village named Majrabari located in the Baksa district of Assam. The method of fieldwork is through a survey of Bodo peasant families, with the help of structured interview schedules interwoven with selected case studies. Our village study is based on 126 peasant families after a house listing of 310 Bodo families. The land market of Majrabari is dominant in sharecropping tenancy arrangements. We noted five agrarian classes in terms of the operation of agricultural land. They are Pure Tenants, Pure Lessors, Owner Operator cum Tenant, Owner Operator cum Lessors, and Owner Operator. Since non-agriculture is also an important contributor to the total earnings of households, we cannot say which of the above classes of land cultivating households are the richest. However, tenant-landowner relationships are not necessarily guided only by impersonal relations in Majrabari. Landowners prefer to lease land to tenants who they have known for a longer duration and can trust. The owners of capital (land, machinery, and irrigation) in this village are a few peasant families belonging to the Basumatari clan, who, incidentally, are also the landed. We see traditional practices of ‘summoning’ exchange labour (saori) during the agricultural season in our study area. We conclude that traditional labour relations co-exist along with modern capitalist agriculture in Majrabari. The credit market is dominant in the informal sector. Although there is a presence of public and private sector banks, including a rural credit cooperative, the dependence of peasant families on moneylenders is high. The village is dominant in the Basumatari clan of Bodos. From this present study, we cannot and do not intend to conclusively claim if a peasant family’s position in a specific clan can be a determining factor of socio-economic class differentiation among the Bodos. However, in the particular context of Majrabari, peasant families of the Basumatari clan seem to be enjoying a privilege over the others in terms of land ownership as well as asset ownership. The petty landowning cultivator classes are relatively better-off. In contrast, the marginal land-owning tenants, as well as the pure tenants, juggle with limited resources to make ends meet. As a result of continuous integration to the market, we see peasant differention in Majrabari. The role of the market notwithstanding, peasants in Majrabari are petty commodity producers. As a result of a small scale of production, the peasant sees little capital accumulation instead funding the reproduction of the means of production from incomes earned elsewhere. With increased costs and little income peasants are increasingly indebted to informal lenders in an under-banked region. Therefore, in an environment of increasing market integration, the Bodo peasantry of Majrabari is also undergoing agrarian distress and proletarianization.
Bedamatta, Rajshree
Keywords: Tribe as Peasant; Peasantization; Debt-induced Land-alienation; Agrarian Transition; Transformation of Tribes; Agrarian Distress; Proletarianization; Tenancy; Indebtedness